INNOVATION OF THE TRADITIONAL SANDSTONE CRAFT PRODUCTS IN THE GLOBALIZATION ERA AT NORTH SINGAPADU VILLAGE GIANYAR - Pendet, I Ketut Muka; Ardhana, I Ketut; Suarka, I Nyoman; Sugiartha, I Gede Arya (E-Journal of Cultural Studies; Volume 10, Number 1, February 2017, 2017)
Nowadays the process through which the sandstone craft products are produced at North Singapadu Village has changed. The appearance of different types of popular sandstone craft products reflecting the local identity produced by the young craftsmen at North Singapadu Village shows this. Such products are different from the traditional sandstone craft ones in terms of form and aesthetic style. Globalization, ideology and technology have basically led to the change. The sandstone industry has become highly innovative. This present study uses the qualitative and interpretative method and the theories used are the theory of acculturation, the theory of deconstruction, and the theory of postmodern aesthetics.              The conclusion of the present study is that the form and process of innovation initially resulted from new ideas and concepts and the craftsmen’s paradigm. The main things which have been responsible for changing the traditional way of life into the modern way of life are formal education, tourism and modern technologies. Those who are positively and negatively affected by globalization are not only the capital owners and craftsmen but the villagers and consumers as well. The sandstone craft products at North Singapadu Village contain the meaning of creativity, the economic meaning, the commodificative meaning and the meaning of cultural change. The finding of the study shows that the craftsmen at North Singapadu Village have ignored the traditional concepts, the technique of producing the products, and the materials used. However, the sandstone craft products at North Singapadu Village do not get extinct but remain to exist and both domestic and foreign consumers are interested in them.